Approaches to enhancing the resilience and independence of smallholder coffee farmers - NB, Mudzakkar; Herlon, Meki; Ridho, Zulhamid; Nurdin, Ibnu Phonna; Andrina, Hanifaturrahmi; Mustaqim, Mustaqim (Enrichment : Journal of Management, 2025)
This study examines strategies to strengthen the self-reliance of smallholder coffee farmers in the Gayo Highlands, focusing on Bener Meriah and Central Aceh Regencies, which are recognized centers of Gayo Arabica coffee production. A strategic analysis approach was applied using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices to assess farmers’ internal strengths and weaknesses alongside external opportunities and threats. The IFE analysis produced a total score of 2.37, indicating a moderate level of internal capacity, driven by long experience in coffee cultivation, strong social cohesion, and favorable agro-climatic conditions. In contrast, the EFE score of 1.98 reflects a relatively weak ability to respond to external dynamics, including global price fluctuations, climate change impacts, and limited market access. Integrating these results into the Internal–External (IE) Matrix places smallholder coffee farmers in Quadrant VI, corresponding to a “Hold and Maintain” strategic posture. This position suggests that empowerment efforts should consolidate existing strengths while addressing vulnerabilities to external pressures. Recommended strategies include upgrading post-harvest technology, expanding direct market access, improving cooperative management, and strengthening climate resilience—steps expected to support sustainable coffee production, reduce dependence on intermediaries, and enhance the competitiveness of Gayo coffee in an increasingly dynamic global market.